Représenter l’activité pour investiguer ses dimensions incarnée, spatio‑temporelle et collective - Clémence Bénézet; Serge Leblanc; Mireille Navarrete; Laure Hossard (Activités)
Farmers involved in agro-ecological transition are testing and adjusting new cropping practices. This process of the step-by-step design of a new agrosystem can be analysed through the description and understanding of farmers’ activity on different spatial and temporal scales and in interaction with multiple human and non-human actors. Our study focuses on the integration of the practice of soil maintenance through horse traction developed over a long period of time by the winegrower in cooperation with a service provider. We mobilize the course-of-action research program (Theureau, 2015) to investigate three dimensions of the activity: embodied, spatio-temporal and collective. We conducted eighteen interviews of different types with three winegrowers and three service providers. To explore each dimension, external representations of the activity, articulated with different theoretical objects and concepts, were developed and used during these interviews to encourage the expression of the actors’ situated experience. This study led to several original results. As long as the researcher is careful to preserve favourable conditions for the actors, the external representations of the activity make it possible to accompany the actors’ explicitation of their situated activity in its three dimensions. These representations facilitate mutual appropriation of the research object by the actors and the researcher, reinforcing the plausibility of the data constructed during the study. Finally, the multidimensional modelling of activity that these representations made possible, might be a resource to support the design of new collaborative experiences between humans and non-humans over time, with and for farmers.